Amelioration of anticorrosion and hydrophobic properties of epoxy/PDMS composite coatings containing nano ZnO particles - Ammar, S.; Ramesh, K.; Vengadaesvaran, B.; Ramesh, S.; Arof, Abdul Kariem (Elsevier, 2016)
Epoxy-polydimethylsiloxane (PDMS) nanocomposite coatings loaded with different concentrations (ranged from 2 to 8% (w/w)) of ZnO nanoparticles have been successfully achieved by using the solution intercalation method. In this study, it has been aimed to investigate corrosion protection performance and hydrophobic properties of epoxy/PDMS nanocomposites (NC). Fourier transform infrared (FTIR) spectroscopy was utilized in order to study the chemical structure of the developed coatings. The coating surface wettability was studied by contact angle measurements and the dispersion of ZnO nanoparticles was examined via field emission scanning electron microscope (FESEM). The effects of ZnO nanoparticles on the corrosion resistance and the barrier performance were investigated by electrochemical impedance spectroscopy (EIS). Thermal properties were evaluated by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) From the FTIR spectra it was observed that the incorporation of nano ZnO particles has demonstrated peak shift and change in intensity. The incorporation of nano ZnO particles within the hybrid polymeric matrix had improved the hydrophobicity in terms of contact angle which reached maximum as 128° for NC6 system. NC2 coating had shown higher coating resistance more than 109 Ω even after 30 days of exposure in electrolyte medium. The results obtained from TGA and DSC studies demonstrated that introducing PDMS to epoxy resin increased Tg whereas the incorporation of ZnO nanoparticles in the nanocomposite coatings showed reduction in degradation temperature, cross-linking density of the composite by lowering Tg.